Evaluation process for GraPE (A web-based expert system for reviewing grant proposal) - Mohd Yusoh, Zeratul Izzah; Shibghatullah, Abdul Samad; Bundy, Alan; Potter, Stephen (2005)
A reviewing process of grant proposals is of paramount importance and tiresome for a referee. It excessively consumes time in reading and analysing the content. However, there is no exact methodology to help and assist referees in the evaluation process. The objective of this vroject is to build a web-based expert system to assist beginner referees in this process The system is based on ERA (Electronic Referee Assistant), la knowledge-based advisor for Informatics research papers, and named GraPE (Grant Proposal ERA ). GraPE aims to provide guidance to beginner referees to help them make a better review and become better reviewers. This paper will describe GraPE and the system evaluation that has been carried out in order to conﬁrm the hypothesis proposed in this project.